Revisiting CD8 T-cell ‘Memory Inflation’: New Insights with Implications for Cytomegaloviruses as Vaccine Vectors - Rafaela Holtappels; Kirsten Freitag; Angelique Renzaho; Sara Becker; Niels A.W. Lemmermann; Matthias J. Reddehase (Vaccines, 2020)
Murine models of cytomegalovirus (CMV) infection have revealed an exceptional kinetics of the immune response. After resolution of productive infection, transient contraction of the viral epitope-specific CD8 T-cell pool was found to be followed by a pool expansion specific for certain viral epitopes during non-productive ‘latent’ infection. This phenomenon, known as ‘memory inflation’ (MI), was found to be based on inflationary KLRG1+CD62L− effector-memory T cells (iTEM) that depend on repetitive restimulation. MI gained substantial interest for employing CMV as vaccine vector by replacing MI-driving CMV epitopes with foreign epitopes for generating high numbers of protective memory cells specific for unrelated pathogens. The concept of an MI-driving CMV vector is questioned by human studies disputing MI in humans. A bias towards MI in experimental models may have resulted from systemic infection. We have here studied local murine CMV infection as a route that is more closely matching routine human vaccine application. Notably, KLRG1−CD62L+ central memory T cells (TCM) and conventional KLRG1−CD62L− effector memory T cells (cTEM) were found to expand, associated with ‘avidity maturation’, whereas the pool size of iTEM steadily declined over time. The establishment of high avidity CD8 T-cell central memory encourages one to pursue the concept of CMV vector-based vaccines.